Turbinicarpus boedekerianus sp. nov. (Cactaceae), a new species from Nuevo León, Mexico - García-Morales, Leccinum Jesús; González-Botello, Miguel Ángel; Matuszewskii, Grzegorz; Nitzschke, Stefan; Iamonico, Duilio (Phytotaxa, 2019)
A new species of Turbinicarpus—Turbinicarpus boedekerianus—from Mexico (Nuevo León, Municipality of Aramberri) is described and compared to the related species Turbinicarpus schmiedickeanus. The new species is morphologically characterized by ocher conic-pyramidal tubercles with an ochraceous waxy layer, a single almost straight and grooved spine, and the white to pale pink to magenta tinged flowers. Ecological data and distribution area in Mexico, as well as the conservation status are provided.